Clinical application of adhesive systems - a critical review: biomimetic approach - Ricci, Weber Adad (2015)
The various functions and clinical applications of adhesive systems have become a fundamental part of restorative treatment. The biggest challenge for such systems is to provide adequate adhesion to the different tissues, which can be very diverse in nature. When choosing the appropriate adhesive system, the dentist should be familiar with the origin, composition, action mechanism and method of application of each system. The commercially available products and their high technical status have made it possible for the clinician to develop a philosophy of maximum tissue preservation, optimized esthetics, up-to-date concepts and procedures and full function of the restored element, compatible with biomimetic theory. The literature describes the superior qualities of results obtained with three-step total etching adhesives and the use of chlorhexidine as a factor to increase longevity. Future perspectives include the use of ethanol, inactivating agents of enzymes released in the adhesive process and the action of agents that act upon the dentin matrix.